The Sublime Void : on the memory of the imagination. - Cassiman, Bart; Antwerpen '93 (Brussel : Koninklijk Museum voor Schone Kunsten, 1993)
Bustamante, Jean-Marc ; Daniëls, René ; De Cordier, Thierry ; Dujourie, Lili ; Fabro, Luciano ; Fortuyn / O'Brien ; Gobert, Robert ; Iglesias, Cristina ; Kemps, Niek ; Klingelhöller, Harald ; Kounellis, Jannis ; Muñoz, Juan ; Murphy, John ; Pistoletto, Michelangelo ; Richter, Gerhard ; Schütte, Thomas ; Spalletti, Ettore ; Tusek, Mitja ; Tuymans, Luc ; Vermeiren, Didier ; Wall, Jeff ; Welling, James ; West, Franz ; Whiteread, Rachel
The Sublime Void : on the memory of the imagination, Koninklijk Museum voor Schone Kunsten, Brussel, 25 July - 10 October 1993. Antw 93, Cultural Capital of Europe
boek